Bullying as the Abuse of Power in Three Selected Picture Books (Universitas Pamulang, 2023)
This study aims at analyzing bullying represented in three selected picture books and how each character resolves the problem through examining verbal and visual texts. The objects of this study are picture books entitled Llama Llama and the Bully Goat (2013), Little Miss Trouble and the Mermaid (2017), and Marlene, Marlene, Queen of Mean (2014). This study applies the qualitative research method as the analysis presented in the form of verbal text and pictures. This study uses the perspective of Peter Hunt (2005) and Kenneth Rigby (2011). The results can shows that the concept caused bullying has many factors such as jealousy, superiority, even only for personal pleasure.